2011
DOI: 10.1080/14767724.2010.513536
|View full text |Cite
|
Sign up to set email alerts
|

ICT or I see tea? Modernity, technology and education in Nepal

Abstract: The use of information and communications technology (ICT) for education in developing countries has been a subject of great interest and speculation, with its proponents arguing that ICT improves educational quality, develops critical thinking skills, expands access, increases economic competitiveness and facilitates inclusion in a rapidly expanding global information society. However, few of these claims have been verified from an empirical standpoint, leading to substantial criticism of the push to expand I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…There is a small body of writings related to the status and practice of ICT in education in Nepal. Several researchers (Dawadi & Shakya, ; Pangeni, ; Rennie & Mason, ; Shields, ) reported the expansion of internet infrastructures throughout Nepal and suggested that these should increase the possibility of e‐learning and enable school teachers to access the latest online information and so facilitate rural school students' education. However, Thapa and Saebo () reported that a lack of high‐quality internet, electricity, and supporting infrastructure are major challenges in Nepal's rural schools.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…There is a small body of writings related to the status and practice of ICT in education in Nepal. Several researchers (Dawadi & Shakya, ; Pangeni, ; Rennie & Mason, ; Shields, ) reported the expansion of internet infrastructures throughout Nepal and suggested that these should increase the possibility of e‐learning and enable school teachers to access the latest online information and so facilitate rural school students' education. However, Thapa and Saebo () reported that a lack of high‐quality internet, electricity, and supporting infrastructure are major challenges in Nepal's rural schools.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The National Curriculum Framework for School Education, 2005 mandated that “ICT as a proven tool for educational transformation” should be used in instructional activities in schools (MoES, , p. 11). Shields () argued that, although the integration of ICT is constituted to meet the national education goal of public service and quality education, the terms proven and transformation in the curriculum are vague and offer no means of evaluating change. The School Sector Development Plan, 2016–23 stated that funding for equipping primary schools with ICT infrastructure is not available (MoE, ) and the ICT Policy, 2015 explicitly stated the government's intention to create public‐private partnerships to provide ICT infrastructure in government schools (MoIC, ).…”
Section: Review Of Literaturementioning
confidence: 99%
“…The use of technology has become another 'compass point' through which individuals (whether students, teachers or policy-makers) and institutions construct modern and progressive identities (Shields, 2011).Based on the observation of digital online tools, used in the low resourced classroom, the following basic tools were found to be used in common the teacher educators as a form of low resourced classroom as best practices in Nepal in the higher studies.…”
Section: Resultsmentioning
confidence: 99%
“…Social inequalities have been exacerbated from the mid-twentieth century aided in no small part by a national education system that excluded minorities' cultures, religions and traditions. Schools and government privileged Nepali as a national language in an attempt to promote a sense of modern Nepal and national citizenship (Shields, 2011). The positioning of Nepali speaking Hindus at the top of a social hierarchy alienated and marginalised many other Nepali ethnic groups from education and political or civic participation (Parker and Standing, 2007;Shields, 2013).…”
Section: Introductionmentioning
confidence: 99%